Effect of different combinations of antimicrobial agents on biological fitness and fecundity of tobacco caterpillar (Spodoptera litura) (Lepidoptera: Noctuidae) reared on meridic diet - SRIDHAR, J; SHARMA, KIRTI (The Indian Journal of Agricultural Sciences, 2026)
Four antifungal and four antibacterial agents in 48 combinations in the meridic diet for investigating their effects on developmental stages of tobacco caterpillar (Spodoptera litura) (Fab.). The antimicrobial combination of D43 recorded significantly higher survival, fecundity, larval (LGI) and total developmental index (TDI). Increasing streptomycin sulphate to 400 ppm in D26 has improved the growth and developmental parameters of insect. Boric acid substituting either formaldehyde (D38) or streptomycin sulphate (D35) in the diet had statistically enhanced the performance of test insect. It is evident that boric acid being an effective antifungal and antibacterial agent at lower concentration can be used to substitute harmful carcinogenic formaldehyde which is needed at highÂ  concentration. However propionic acid, chloramphenicol and oxytetracyclin showed significant negative effects on the biological performance of insect. This work brings out diets, D26, D35, D38, D42, D43 and D46 giving good results as far as biological parameters are concerned.